Internalisasi Nilai-nilai Kewarganegaraan dalam Pembelajaran IPS Studi Perspektif Guru dan Siswa Sekolah Menengah Pertama Simpang Hulu: Internalization of Civic Values in Social Studies Learning: A Study of the Perspectives of Teachers and Students at Simpang Hulu Junior High School - Simon Sinto; Hana Mauludea (ITScience (Information Technology and Science), 2026)
The phenomenon of juvenile delinquency, low social awareness, and suboptimal character formation in the school environment indicates that the internalization of civic values remains a challenge in educational practice. Social Studies (IPS) learning plays a strategic role as a medium for instilling values, but its implementation has not fully enabled consistent changes in student behavior. This study aims to analyze the process of internalizing civic values in IPS learning through the perspectives of teachers and students at Simpang Hulu Junior High School. The study used a qualitative, descriptive approach. Data were collected through observation, in-depth interviews, and documentation, involving IPS teachers and students as research subjects. Data analysis used Miles, Huberman, and Saldaña's interactive model through the stages of data reduction, data presentation, and conclusion drawing. The study identified three main points. First, values are internalized through the integration of values into learning materials, habituation in learning activities, and role modeling by teachers. Second, teachers have a strong awareness of the importance of instilling civic values, whereas students interpret values situationally, based on their learning experiences and peer environments. Third, there is a gap between students' cognitive understanding of values and consistent behavioral practices in everyday life. This study concludes that the internalization of civic values in social studies learning is a dynamic process influenced by individual factors, the social environment, and pedagogical approaches. Strengthening participatory and experiential learning is necessary for more effective internalization of civic values in students.